2005
DOI: 10.1001/jama.294.8.924
|View full text |Cite
|
Sign up to set email alerts
|

Screening Healthy Infants for Iron Deficiency Using Reticulocyte Hemoglobin Content

Abstract: A CHr of less than 27.5 pg is a more accurate hematological indicator of iron deficiency compared with hemoglobin of less than 11 g/dL in these healthy 9- to 12-month-old infants. Further studies are warranted to determine whether CHr should be the preferred screening tool in the early detection of iron deficiency in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 39 publications
7
133
0
9
Order By: Relevance
“…Our study shows that retHe is superior to this panel of tests in the detection of iron deficiency as early as its latent stage. This is in accordance with previous reports [13][14][15][16], which showed that determination of the reticulocyte hemoglobin content may allow realtime evaluation of iron deficiency and concluded that it is to be used as a marker of iron deficiency. Failure of RetHe to predict the prelatent stage of iron deficiency can be overcomed by a close look at the RDW CV % which is significantly increased compared to normal controls (p<0.0005).…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows that retHe is superior to this panel of tests in the detection of iron deficiency as early as its latent stage. This is in accordance with previous reports [13][14][15][16], which showed that determination of the reticulocyte hemoglobin content may allow realtime evaluation of iron deficiency and concluded that it is to be used as a marker of iron deficiency. Failure of RetHe to predict the prelatent stage of iron deficiency can be overcomed by a close look at the RDW CV % which is significantly increased compared to normal controls (p<0.0005).…”
Section: Discussionsupporting
confidence: 93%
“…identifying non-anemic iron deficiency defined by ferritin concentration, 28 and in infants, an AUC ROC of 0.85 when iron deficiency was defined by transferrin saturation. 29 We found that serum hepcidin, when compared with the sTfR-F index gold standard, had an AUC ROC of 0.89, and when compared with ferritin, the AUC ROC was 0.87. Hepcidin is, therefore, at least as promising as other recently introduced tests of iron deficiency.…”
Section: S-r Pasricha Et Almentioning
confidence: 71%
“…Two studies have examined the clinical utility of CHr in pediatric patients (age 9 months to 8 years) with comparison to other markers. The optimal CHr concentration cutoff value for the diagnosis of iron deficiency differed slightly in these two studies at 26.0 and 27.5 pg [11,12]. CHr outperformed ferritin, MCV, MCH, RDW, and Zn protoporphyrin in detecting iron deficiency defined by decreased hemoglobin and transferrin saturations.…”
Section: Applications and Limitationsmentioning
confidence: 86%